Carbonyl (CO)/N-based thermally activated delayed fluorescent materials with high efficiency and fast reverse intersystem crossing rate: a theoretical design and study. (31st March 2023) - Jiang, Shanshan; Qi, Fangfang; Zhang, Donghai; Lv, Xin; Song, Jinhui; Gu, Junjing; Chen, Jinglin; Meng, Lingyi
Abstract : Two novel highly efficient organic TADF materials based on MR structures have been theoretically designed and investigated. Abstract : Thermally activated delayed fluorescence (TADF) materials based on multiple resonance (MR) molecular structures can achieve advantages, such as high fluorescence efficiency, reduced structural relaxation and narrow emission. It still remains a challenge to design highly efficient MR structure-based TADF materials with fast reverse intersystem crossing processes and easy emission-color tuning. Herein, we theoretically investigated the recently reported TADF molecule, which has the MR structure of quinolino[3, 2, 1- de ] acridine-5, 9-dione (QAD) as the acceptor and the moiety of carbazole (Cz) as the donor, namely QAD-Cz. The calculated fluorescence quantum efficiency of QAD-Cz is as high as 96.5%, which agrees with the experimental results (99.6%) very well. Moreover, we designed two new TADF materials based on the MR-QAD structure with different electron-donating moieties, namely QAD-TPA and QAD-DPTZ. The two newly designed molecules can theoretically achieve high fluorescence quantum efficiencies (over 90%) and fast reverse intersystem crossing rates ( e.g. as high as 10 7 s −1 for QAD-DPTZ). The calculated emission wavelength of the QAD-DPTZ molecule is 638 nm, which obviously widens the emission color range of the reported MR-QAD-based TADF materials. Furthermore, we have analyzed the aggregation effects of the QAD-DPTZ molecule and demonstrated that this novel compound can likewise exhibit excellent luminescence performance in amorphous states.